Central GABAA receptor mediates taurine-induced hypothermia and possibly reduces food intake in thermo-neutral chicks and regulates plasma metabolites in heat-exposed chicks. (May 2021) - Elhussiny, Mohamed Z.; Tran, Phuong V.; Pham, Cuong V.; Nguyen, Linh T.N.; Haraguchi, Shogo; Gilbert, Elizabeth R.; Cline, Mark A.; Bungo, Takashi; Furuse, Mitsuhiro; Chowdhury, Vishwajit S.
Abstract: The aim of this study was to examine the central action of taurine on body temperature and food intake in neonatal chicks under control thermoneutral temperature (CT) and high ambient temperature (HT). Intracerebroventricular injection of taurine caused dose-dependent hypothermia and reduced food intake under CT. The mRNA expression of the GABAA receptors, GABAA R-α1 and GABAA R-γ, but not that of GABAB R, significantly decreased in the diencephalon after central injection of taurine. Subsequently, we found that picrotoxin, a GABAA R antagonist, attenuated taurine-induced hypothermia. Central taurine significantly decreased the brain concentrations of 3-methoxy-4-hydroxyphenylglycol, a major metabolite of norepinephrine; however, the concentrations of serotonin, dopamine, and the epinephrine metabolites, 3, 4-hydroxyindoleacetic acid and homovanillic acid, were unchanged. Although hypothermia was not observed under HT after central injection of taurine, plasma glucose and uric acid levels were higher, and plasma sodium and calcium levels were lower, than those in chicks under CT. In conclusion, brain taurine may play a role in regulating body temperature and food intake in chicks through GABAA R. The changes in plasma metabolites under heat stress suggest that brain taurine may play an important role in maintaining homeostasis in chicks. Highlights : Central injection of taurine reduces body temperature and food intake . Central GABA A receptor mediates taurine-induced hypothermia . Brain taurine decreases plasma calcium under heat stress . Central taurine causes the increase in plasma glucose and uric acid under heat stress .